Regional nitrogen dynamics in the TERENO Bode River catchment, Germany, as constrained by stable isotope patterns. Issue 1 (3rd March 2016) - Mueller, Christin; Krieg, Ronald; Merz, Ralf; Knöller, Kay
Abstract : Interactions between hydrological characteristics and microbial activities affect the isotopic composition of dissolved nitrate in surface water. Nitrogen and oxygen isotopic signatures of riverine nitrate in 133 sampling locations distributed over the Bode River catchment in the Harz Mountains, Germany, were used to identify nitrate sources and transformation processes. An annual monitoring programme consisting of seasonal sampling campaigns in spring, summer and autumn was conducted. δ 15 N and δ 18 O of nitrate and corresponding concentrations were measured as well as δ 2 H and δ 18 O of water to determine the deuterium excess. In addition, precipitation on 25 sampling stations was sampled and considered as a potential input factor. The Bode River catchment is strongly influenced by agricultural land use which is about 70 % of the overall size of the catchment. Different nitrogen sources such as ammonia (NH4 ) fertilizer, soil nitrogen, organic fertilizer or nitrate in precipitation show partly clear nitrate isotopic differences. Processes such as microbial denitrification result in fractionation and lead to an increase in δ 15 N of nitrate. We observed an evident regional and partly temporal variation of nitrate isotope signatures which are clearly different between main landscape types. Spring water sections within the high mountains contain nitrate in low concentrations with low δ 15 NNO3 values of −3 ‰ and high δ 18 ONO3 values up to 13 ‰. High mountain stream water sub-catchments dominated by nearly undisturbed forest and grassland contribute nitrate with δ 15 NNO3 and δ 18 ONO3 values of −1 and −3.5 ‰, respectively. In the further flow path, which is affected by an increasing agricultural land use and urban sewage, we recognized an increase in δ 15 NNO3 and δ 18 ONO3 up to 22 and 18 ‰, respectively, with high variations during the year. A correlation seems to exist between the percentage of agricultural land use area and the corresponding δ 15 NNO3 values for sub-catchments. A shift towards heavier isotope values in stream water samples taken in July 2012 is significant ( p -value = 6 · 10 −6 ) compared to samples from March and October 2012. We also see a season-depending impact of microbial denitrification. Denitrification, especially evident in the lowlands, predominantly takes place in the riverbeds. In addition, mixing processes of different nitrate sources and temperature-depending biological processes such as nitrification have to be taken into consideration. Constant-tempered groundwater does not play a noticeable role in the processes of the stream water system. As constrained from oxygen isotope signatures, precipitation associated with low nitrate concentrations does not have an obvious impact on stream water nitrate in the high mountain region.